Phenolic compounds and antioxidant activity of edible flowers - Skrajda, Marta Natalia (Journal of Education, Health and Sport, 2017)
Introduction: Edible flowers has been used for thousands of years. They increase aesthetic appearance of food, but more often they are mentioned in connection with biologically active substances. The main ingredient of the flowers is water, which accounts for more than 80%. In small amounts, there are also proteins, fat, carbohydrates, fiber and minerals. Bioactive substances such as carotenoids and phenolic compounds determine the functional properties of edible flowers. Aim: The aim of this work was to characterize the phenolic compounds found in edible flowers and compare their antioxidant activity. Results: This review summarizes current knowledge about the usage of edible flowers for human nutrition. The work describes the antioxidant activity and phenolic compounds of some edible flowers. Based on literature data there is a significant difference both in content of phenolic compounds and antioxidant activity between edible flowers. These difference reaches up to 3075-fold in case of antioxidant potential. Among described edible flowers the most distinguishable are roses, peonies, osmanthus fragans and sambuco nero. Conclusions: Edible flowers are the new source of nutraceuticals due to nutritional and antioxidant values.